2002
DOI: 10.1038/sj.bmt.1703734
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of G-CSF mobilisation on dendritic cell subsets in normal allogeneic donors and patients undergoing autologous transplantation

Abstract: Summary:It has been suggested that the immunological properties of cytokine primed PBSC may reflect the presence of altered levels of cellular components. In this study the changes induced in blood dendritic cell (DC) subsets following G-CSF mobilisation are analysed. Analysis of normal donors (n = 64) demonstrated considerable individual variation in the absolute numbers (؋10 6 /l) of resting blood CD11c ؊ DC (1.2-26.2) and CD11c + DC (0.9-34.7) as well as in the CD11c ؊ /CD11c + DC ratio (0.29-4.13). G-CSF t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…For example, GM-CSF will (a) enhance the tumor-directed lytic ability of PBMNC; (b) activate macrophages and (c) mediate the proliferation, maturation and migration of dendritic cells. In addition, GM-CSF mobilization may enhance innate and acquired immunity after transplant, because it decreases the number of type 2 dendritic cells (DC2) within the mobilized cells (30,31). These dendritic cells may inhibit cellular immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, GM-CSF will (a) enhance the tumor-directed lytic ability of PBMNC; (b) activate macrophages and (c) mediate the proliferation, maturation and migration of dendritic cells. In addition, GM-CSF mobilization may enhance innate and acquired immunity after transplant, because it decreases the number of type 2 dendritic cells (DC2) within the mobilized cells (30,31). These dendritic cells may inhibit cellular immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have studied the polarization of DC subsets during PBSC mobilization with G-CSF in normal donors (22)(23)(24)(25) for allogeneic transplantation and in cancer patients (26). Several groups reported polarization to pDC2 cells in normal donors receiving G-CSF for mobilization (22)(23)(24)28,29), whereas others did not find polarization to pDC2 (26,27,30).…”
Section: Introductionmentioning
confidence: 94%
“…It has been reported that mobilization of PBSCs with G-CSF results with polarization of DCs to pDC2-type DC subset, resulting with an increase in Th2-type over Th1-type T cell response with a potential for a decrease in overall T cell cytotoxicity (23)(24)(25)(26)(27)(28)(29)(30). Because the effect of AMD3100 on mobilization of DCs was never tested before, we decided to test the effect of adding AMD3100 to NHL patients mobilized with G-CSF on blood pDC1 and pDC2 cells.…”
Section: Mobilization Of Dendritic Cellsmentioning
confidence: 99%
“…24,[34][35][36] G-CSF, although regarded by some as a Th2-inducing cytokine, seems to have inconsistent effects in terms of Th1/Th2 skewing. It has been shown that G-CSF can exert immunomodulatory effects on T lymphocytes and affect the production of IFN-g and IL-4, possibly owing to the preferential mobilization of Th2-inducing DCs.…”
Section: Discussionmentioning
confidence: 99%